Augmented Reality-Oriented Problem-Based Learning in Natural Science Materials - Wiraha, Made Adi; Sudarma, I Komang (International Journal of Elementary Education, 2023)
Problems that arise from students' difficulties in participating in the learning process and working on media for a long time make students' abilities low. Student learning outcomes are common because the lack of student knowledge is the main problem in learning. To help improve student learning outcomes can be assisted by using learning media, this study uses augmented reality learning media. This study aims to design problem-based learning based on augmented reality on science material for class V. This research uses a quantitative method. The subjects in this study consisted of 1 media expert, one design expert, and one content expert; three students as individual trials, nine as small group trials, and 23 as field trials. Data collection techniques include qualitative description, quantitative description, and statistical inferential t-test. The results of the study were (1) the design of augmented reality with the ADDIE model stages, (2) the media expert scored 94.4% very good qualification, the design expert test scored 92% very good qualification, the content expert test scored 98.6% qualification very good, individual trials obtained a score of 96.47% very good qualification, group trials obtained a score of 95.57% very good qualifications, (3) based on the effectiveness test it was declared effective, based on the average pretest results with a score of 49.2 and the average posttest results with a score of 84.78. It can be concluded that problem-based learning-oriented augmented reality in science material is feasible.